Fully Bio-based Aromatic Polyimide Using 4-Aminocinnamic Acid and Mellophanic Dianhydride as Bio-derived Monomers. (13th December 2018) - Takada, Kenji; Karikome, Satoru; Dwivedi, Sumant; Kaneko, Tatsuo
Abstract : Mellophanic dianhydride which is aromatic tetracarboxylic dianhydride monomer for synthesis of polyimide, were derived from maleic anhydride and 2, 5-dimethylfuran as the bio-derived monomers with the new approach. The obtained mellophanic dianhydride is used to synthesize the fully bio-based poly(amic acid) using 4-aminocinnamic acid dimer as the bio-based aromatic diamine monomer. For controlling the solubility of polyimide, thermal or chemical imidizations are carried out by using stepwise heating method or acetic anhydride/pyridine treatment, respectively. Thermally imidized polyimides show low solubility for organic solvent, however, chemically-imidized polyimide show good solubility for N -methyl-2-pylloridione, dimethylsulfoxide, and N, N -dimethylformamide. In addition, all the obtained polymers show high heat resistance properties, 10 % decomposed temperature ( T d10 ), of poly(amic acid) is 331 °C, while T d10 of polyimides are 389 °C regardless of imidization processes. Thus, fully bio-based polyimides having high thermostability is developed for the first time.